Analisis Penggunaan Big Book Terhadap Literasi Membaca Peserta Didik Berkecerdasan Visual di Madrasah Ibtidaiyah Nahdlatul Ulama Waru 1 Sidoarjo - M. Amin; Choirotun Nisa’; Bachtiar Hariyadi (Universitas Yudharta Pasuruan, 2021)
This study aims to find out if there are differences in the use of big books on reading literacy between visually educated students and non-visual students at MINU Waru 1. This study uses a quantitative approach with a type of comparison. The study population was 84 students in grade 1, with a sample of 64 students divided into grades 1A, 1B, and 1C. Through observation, students are classified their intelligence levels and with tests to measure reading literacy levels. The results were analyzed using independent sample t-test that was previously done prerequisite test, namely normality test and homogeneity test, using SPSS application version 22. Independent sample t-test results showed a significance value of < 0.05 is (0.000 < 0.05) for the pretest, and a significance value of < 0.05 is (0.008 < 0.05) for posttest. From these results, Ho was rejected and Ha received which means there is a difference in the use of big book media to read literacy between grade I students who have visual intelligence and non-visual students at MINU Waru 1 Sidoarjo